The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/fcsr.12099
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Student Loan Decisions: A Literature Review

Abstract: Because of the continuing increase in college costs and the need for a college education, the use of student loans has affected many individuals and households in the United States. Researchers and policy-makers need a comprehensive review of literature to understand the determinants and consequences of student loans. This article provides information on the current trends in student loans, reviews the effect of education loans on college enrollment and career decisions, as well as the effects on personal life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 72 publications
0
38
0
4
Order By: Relevance
“…Prior research finds, however, that student borrowing is associated with other health indicators, regardless of race/ethnicity 5 18 19. Our study suggests that a more nuanced view of the association between student borrowing and health is needed and that research on the impact of student borrowing on health should focus on those who are at greater risk of both poor health and student borrowing.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Prior research finds, however, that student borrowing is associated with other health indicators, regardless of race/ethnicity 5 18 19. Our study suggests that a more nuanced view of the association between student borrowing and health is needed and that research on the impact of student borrowing on health should focus on those who are at greater risk of both poor health and student borrowing.…”
Section: Discussionmentioning
confidence: 64%
“…Since student loans may be a major source of financial stress for many young adults,18 19 we hypothesise that borrowing greater amounts of student loans will be associated with shorter sleep duration. We further investigate differences by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists that student loan debt is negatively associated with homeownership (Brown, Haughwout, Lee, Scally, & van der Klaauw, ; Cho, Xu, & Kiss, ; Houle & Berger, ; Shand, ). Elliott, Grinstein‐Weiss, and Nam () found that the median home equity of households with no student debt ($90,000) was twice that of households with student debt ($45,000) in 2009.…”
Section: Internal Factorsmentioning
confidence: 99%
“…In addition, student loan debt registers the highest delinquency rate of all consumer debt products (Cangero, 2017). Student loan debt also effects other areas of the borrower's personal and financial life, such as their health, financial capability, homeownership, and retirement savings (Cho, Xu, & Kiss, 2015;O'Neill, Xu, Johnson, Kiss, & Buyske, 2019;Xu, Johnson, Bartholomae, O'Neill, & Gutter, 2015).…”
mentioning
confidence: 99%